Effect of Feeding Sugarcane Byproduct Based Ration on Growth and Carcass Traits of Male Buffalo Calves - Kumar, R. Prasanna; Kumar, M. Shashi; Rani, Sahitya (Journal of Meat Science, 2014)
An experiment was conducted to study the effect of feeding sugarcane byproduct based ration on growth, nutrient utilization and carcass characteristics of male buffalo calves. Six rations which includes five complete rations (CR-I to CR-V) and one conventional ration as control were studied. Highest average daily gain (ADG) (610.0g) was recorded in buffalo bull calves fed on complete ration-II (Sugarcane tops, maize stover and balanced concentrate mixture) when compared among the complete rations and control. The cost of production per kg live weight gain was Rs.41.14 in control group. The cost of production per kg live weight gain was insignificantly higher in control than complete rations. The cost of production per kg live weight was reduced by Rs.3.11, 8.69, 8.60, 10.92 and 8.10 for complete rations-I, II, III, IV and V, respectively, when compare to control diet. The dressing percentage on live weight was significantly (P<0.05) lower in male calves fed on complete rations than those fed on control ration. These results indicated that the sugarcane by-products and other crop residues can be incorporated in the complete rations in growing buffalo calves without any adverse effects. Further, utilization of agro-industrial by-products for animal production can effectively bridge the gap of roughage shortage in this country.